REACTIVATION OF HUMAN ENDOGENOUS RETROVIRUSES (HERV-W) AS A GENETIC-IMMUNOLOGICAL TRIGGER OF PSYCHOSIS: A REVIEW OF THE NEUROTOXIC MECHANISMS OF THE ENVELOPE PROTEIN (ENV) - Jakub Robert Skalski; Łukasz Ćmok; Justyna Chudy; Julia Jadwiga Dobrowolska; Gabriela Daniel; Natalia Kaczmarczyk; Antoni Hajdas; Karolina Halat; Julia Szmuc; Iga Kałka (International Journal of Innovative Technologies in Social Science, 2026)
Schizophrenia does not arise from a single genetic flaw or a solitary environmental insult; rather, it is born from the collision of both. In this review, we move beyond classical neurotransmitter theories to dissect the molecular pathogenicity of the Human Endogenous Retrovirus-W Envelope protein (HERV-W ENV). We trace the evolution of the historical "viral hypothesis" into the modern "two-hit" model, wherein environmental stressors literally awaken dormant retroviral elements within our own DNA. How does this intragenomic parasite damage the brain? We evaluate its neurotoxicity across three distinct pillars: structural, immunological, and signaling. Structurally, the protein’s fusogenic properties induce severe membrane instability. Immunologically, it acts as a potent toxin, igniting the microglial TLR4 cascade and driving neurons into violent, inflammatory death via the NLRP3-Caspase-1-GSDMD pyroptosis pathway. Yet, the most profound damage occurs within intracellular signaling. HERV-W ENV actively sabotages the dopamine-glutamate axis. It forces NMDA receptors to escape the synapse laterally, starves the synaptic cleft by blocking ASCT1/2-mediated glutamine transport, and hijacks the AKT/GSK3β pathway to drive dopaminergic hyperactivity. These integrated mechanisms establish HERV-W ENV not just as a bystander, but as a direct causal bridge between immune dysregulation and synaptic failure. Recognizing this distinct "inflammatory biotype" of psychosis completely alters the therapeutic landscape. We conclude by exploring how neutralizing this viral protein with the monoclonal antibody Temelimab could move the field from symptomatic management toward true etiological intervention in precision psychiatry.